Enhancing our understanding of the time course of acute exacerbations of COPD managed on an outpatient basis - Oliveira, Ana (2019)
Purpose: Acute exacerbations of COPD (AECOPD) are associated with pulmonary/systemic changes; however, quantification of those changes during AECOPD managed on an outpatient basis and factors influencing recovery are lacking. This study aimed to characterize patients’ changes during AECOPD and identify factors influencing their recovery. Methods: Body mass index, the modified British Medical Research Council questionnaire, number of exacerbations in the previous year, and the Charlson comorbidity index (independent variables) were collected within 24–48 hours of hospital presentation (T0). Peripheral oxygen saturation (SpO2), forced expiratory volume in one second, percentage predicted (FEV1% pre-dicted), maximum inspiratory pressure, quadriceps muscle strength, 5 times sit-to-stand, and COPD assessment test (CAT) (dependent variables) were collected at T0 and approximately at days 8 (T1), 15 (T2), and 45 (T3) after T0. Results: A total of 44 outpatients with AECOPD (31♂; 68.2±9.1 years; 51.1±20.3 FEV1% predicted) were enrolled. All variables improved overtime (P<0.05); however, at day 8, only SpO2 and CAT (P≤0.001) showed significant improvements. Changes in FEV1% predicted and SpO2 were not influenced by any independent measure, while changes in other outcome measures were influenced by at least one of the independent measures. Independently of the time of data collection, being underweight or overweight and having increased dyspnea, previous exacerbations, and severe comorbidities negatively affected patients’ outcomes. Conclusion: FEV1% predicted and SpO2 were not influenced by any independent measure and, thus, seem to be robust measures to follow-up outpatients with AECOPD. No single indicator was able to predict patients’ recovery for all measures; thus, a comprehensive assessment at the onset of the AECOPD is required to personalize interventions.